The Effect of Family Atmosphere on Chinese College Students’ Pro-social Behavior: The Chained Mediation Role of Gratitude and Self-Efficacy - Li, Na; Li, Qiangqiang (Frontiers in Psychology, 2022)
The current study aimed to explore how family atmosphere influenced pro-social behavior among Chinese college students and to explore the mediation roles of gratitude and self-efficacy. We recruited 800 Chinese college students, and the participation rate was 89% (712 participants, M = 19.26, SD = 1.23). Participants completed the family atmosphere scale, the pro-social tendencies measure, the gratitude questionnaire, and the general self-efficacy scale. Results indicated that (1) family atmosphere, gratitude, self-efficacy, and pro-social behavior were positively correlated after controlling for the grade, gender, and age. (2) The family atmosphere affected pro-social behavior not only directly, but also indirectly through the partial mediating role of gratitude and self-efficacy. Moreover, gratitude and self-efficacy also played a full chained mediation role in the relationship between the family atmosphere and pro-social behavior of college students. Therefore, a supportive family atmosphere is conducive to promoting college students’ gratitude and self-efficacy, in turn affecting their pro-social behavior.